Decreased Corticospinal Excitability after the Illusion of Missing Part of the Arm - Kilteni, Konstantina; Grau-Sánchez, Jennifer; Veciana De Las Heras, Misericordia; Rodríguez-Fornells, Antoni; Slater, Mel (Frontiers in Human Neuroscience, 2016)
Previous studies on body ownership illusions have shown that under certain multimodal conditions, healthy people can experience artificial body-parts as if they were part of their own body, with direct physiological consequences for the real limb that gets ‘substituted’. In this study we wanted to assess (a) whether healthy people can experience ‘missing’ a body-part through illusory ownership of an amputated virtual body, and (b) whether this would cause corticospinal excitability changes in muscles associated with the ‘missing’ body-part. Forty right-handed participants saw a virtual body from a first person perspective but for half of them the virtual body was missing a part of its right arm. Single pulse transcranial magnetic stimulation was applied before and after the experiment to left and right motor cortices. Motor evoked potentials (MEPs) were recorded from the first dorsal interosseous (FDI) and the extensor digitorum communis (EDC) of each hand. We found that the stronger the illusion of amputation and arm ownership, the more the reduction of MEP amplitudes of the EDC muscle for the contralateral sensorimotor cortex. In contrast, no association was found for the EDC amplitudes in the ipsilateral cortex and for the FDI amplitudes in both contralateral and ipsilateral cortices. Our study provides evidence that a short-term illusory perception of missing a body-part can trigger inhibitory effects on corticospinal pathways and importantly in the absence of any limb deafferentation or disuse.